2016
DOI: 10.1007/s40272-016-0183-3
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-Head Comparison of Aripiprazole and Risperidone in the Treatment of ADHD Symptoms in Children with Autistic Spectrum Disorder and ADHD: A Pilot, Open-Label, Randomized Controlled Study

Abstract: Our study confirms the efficacy of both aripiprazole and risperidone in ameliorating ADHD symptoms of children also presenting with ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 64 publications
5
22
1
Order By: Relevance
“…In particular, three patients in the aripiprazole group had PRL level below the normal range (2-18 ng/mL). This is consistent with findings obtained by a previous investigation (31).…”
Section: Monitoring Of Parameters Over Timesupporting
confidence: 94%
See 3 more Smart Citations
“…In particular, three patients in the aripiprazole group had PRL level below the normal range (2-18 ng/mL). This is consistent with findings obtained by a previous investigation (31).…”
Section: Monitoring Of Parameters Over Timesupporting
confidence: 94%
“…Our study has found no statistically significant differences in patients treated continuously for 1 year with risperidone or aripiprazole in relation to fasting glucose, total cholesterol, and triglycerides, as well as in white blood cell concentration and neutrophil percentage. These findings are in agreement with scientific literature (25,31) and support the relative safety of these two APs in terms of these metabolic parameters.…”
Section: Monitoring Of Parameters Over Timesupporting
confidence: 92%
See 2 more Smart Citations
“…Lamberti et al compared risperidone and aripiprazole in the treatment of attention deficit hyperactivity (ADHD) symptoms in children with ASD, with 37 of the children completing the 24 weeks of treatment. They suggested that both aripiprazole and risperidone are effective in ameliorating the ADHD symptoms in ASD (Lamberti et al 2016). Moreover, Ghanizadeh and Sahraeizadah (2014) reported that the safety and efficacy of aripiprazole and risperidone were comparable in their head-to-head comparison study.…”
Section: İlker Tascimentioning
confidence: 99%